Impact of sprouted gram and mung flour on iron, calcium, dietary fiber, and vitamin C content in biscuits - Gupta, Sonam; Bhatt , Devender Kumar (Journal of Postharvest Technology, 2023)
This study aimed to investigate the potential impact of sprouted gram and mung flour on the nutritional content of biscuits. Six variations of biscuits were prepared, each with different ratios of refined flour, sprouted gram flour, and sprouted mung flour. All samples contained 1 gram of baking powder, 1 gram of baking soda, 60 grams of sugar, 50 grams of butter, and sufficient water to make a soft dough. The results of the study showed that the incorporation of sprouted gram and mung flour into biscuits led to an increase in Calcium and Vitamin C content. Sample T3, which contained 70% refined flour, 15% sprouted gram flour, and 15% sprouted mung flour, had the highest levels of Calcium (260 ± 25.1 mg/100g) and Vitamin C (26.1 ± 0.406 mg/100g). The analysis conducted to determine the iron content in all six samples was unsuccessful as the results were below the limit of quantification (BLQ), implying that the iron concentration was too low to be accurately measured using the employed method. In conclusion, the incorporation of sprouted gram and mung flour into biscuits can increase their nutritional value. Therefore, these flours can be considered as an alternative ingredient in the production of biscuits. Further studies could explore the potential impact of sprouted gram and mung flour on other nutritional components of baked goods.